Team based labour assignment methodology for new product development projects. (April 2017) - Baysan, Serdar; Durmusoglu, M. Bulent; Cinar, Didem
Highlights: We develop a team based labour assignment methodology for NPD projects. Proposed hierarchical methodology integrates VSM, DSM and clustering techniques. The aim is to eliminate waste and create flow to reduce lead time. A real life application is performed to evaluate the proposed methodology. The results tested by simulation have promised significant lead time reduction. Abstract: This study explores the organizational aspects of new product development projects and proposes a new team-based labour assignment methodology. The proposed hierarchical methodology focusses on the project value stream and aims to shorten lead time through waste reduction. Lean product development tools, such as clustering and design structure matrix tools, are integrated with the methodology. A detailed real-life case study is presented and the proposed methodology is evaluated using discrete event simulation. Experiment results show that the proposed methodology and team-based structure provide superior lead time performance when compared to conventional organizational setting. This study contributes to existing literature by presenting evidence of the effect of teams on NPD lead time performance.